Trust based Identity Provisioning for Cloud Computing - Aradhana (My University, 2011)
Cloud computing is current buzzword in the market. It is paradigm in which the resources can be leveraged on per use basis thus reducing the cost and complexity of service providers. Cloud computing promises to cut operational and capital costs and more importantly let IT departments focus on strategic projects instead of keeping datacenters running. It is much more than simple internet. It is a construct that allows user to access applications that actually reside at location other than user’s own computer or other Internet-connected devices. There are numerous benefits of this construct. For instance other company hosts user application. This implies that they handle cost of servers, they manage software updates and depending on the contract user pays less i.e. for the service only. Despite of so many cloud benefits its usage has been hindered due to security issues which need to be addressed. Identity management in cloud requires new dimensions to be understood. In a federated environment a seamless interaction is required between service providers and identity providers thus increasing user experience. This necessitates building of dynamic trust relationships for efficient federated identity management. In this thesis current identity frameworks have been compared, importance of Trust in Identity management has been analyzed and risk factor has been incorporated in Trust Management. Further Trust policies have been designed and validated on Google App Engine using Python.
M.E. (Software Engineering)
Keywords: Cloud Computing; Trust Model